Síndrome del Desfiladero Torácico en una niña - Caceres, Juan Pablo (Revista Argentina de Neurocirugía, 2021)
The Thoracic Outlet Syndrome (TOS) conforms series of symptoms and signs caused by a compression of the neurovascular structures in the output thoracic pass at supraclavicluar level2. Depending on the affected structure, the syndrome can be Nerve Thoracic Outlet Syndrome (NTOS), Arterial Thoracic Outlet Syndrome (ATOS) or Venous Thoracic Outlet Syndrome (VTOS).3 The presentation in childhood is exceptional and the appearance with motor deficits occurs in one in a million cases.1 The main clinical signs of TOS in adults include ip-silateral upper limb pain and discomfort, weakness, cold intolerance, and numbness of the hand. During physical examination, the muscles of the ipsilateral limb are relatively weak, and anesthesia, or pinprick sensation without pain is present on the inner sur- face of the hand and forearm. Thenar and hypothenar muscle atrophy may also be seen. In contrast, in children and teenagers, TOS usually presents as neck discomfort, upper limb numbness, weakness, and sensory loss.9 We present the case of an 8-years-old girl started symptomatology coinciding with a biopsy taken for supraclavicular tumor at this level.